1965
DOI: 10.1172/jci105291
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of action of unsaturated fats on cholesterol metabolism in the rabbit.

Abstract: The original observation by Kinsell and his associates (3) and by Groen and his associates (4) that the feeding of saturated fats results in an elevation whereas the feeding of unsaturated fats causes a lowering of serum cholesterol has been confirmed repeatedly in both man (5-7) and experimental animals (7-10). Theoretically, unsaturated fats might produce a lowering of serum cholesterol in at least four ways: by increasing the excretion or degradation of cholesterol, by inhibiting cholesterol synthesis, by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

1969
1969
1984
1984

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Further, the composition of fatty acids such as linoleate, may influence cholesterol metabolism. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). We found that linoleate had no effect on the half-life of cholesterol, though it lowered plasma cholesterol (20).…”
mentioning
confidence: 94%
“…Further, the composition of fatty acids such as linoleate, may influence cholesterol metabolism. (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). We found that linoleate had no effect on the half-life of cholesterol, though it lowered plasma cholesterol (20).…”
mentioning
confidence: 94%
“…1, locus A) or by increasing secretion of cholesterol into the intestinal tract (locus C); an increase in bile acid excretion could be due to a decreased reabsorptionof bile acids (locus B) or to an increased conversion of cholesterol into bile acids (locus E). The hypocholesterolemic effect of unsaturated fats might also be due to decreased synthesis of cholesterol (locus D) (10), or to a redistribution of cholesterol from plasma into tissues (loci F and G) (11)(12)(13). In our view, the present confusion has several possible origins: results obtained from various animal species may not be applicable directly to man; patients with different kinds of lipid abnormalities may not respond by identical mechanisms to diets containing unsaturated fats; experimental designs may have been inappropriate to resolve the problem; or the methods used to describe the various aspects of cholesterol metabolism may not have been sufficiently critical or precise.…”
mentioning
confidence: 99%
“…With more liberal feeding of the diets in the second trial, dry matter and fat percentages were greater in beef-and soy-fed pigs than in conven tionally-fed pigs, again paralleling differences seen in carcass and whole body parameters. Cholesterol concentra tion, however, was greatest in pigs fed the essentially terol concentrations in several species, including rats (Wiggers et al, 1977;, rabbits (Bieberdorf and Wilson, 1965;Richard et al, 1982), guinea pigs , squirrel monkeys (Lofland et al, 1970), calves Barrows et al, 1980), goats , and pigs (Kim et al, 1978;, and protein and(or) fat in the diet may be responsible for the differences in tissue cholesterol content between dietary groups in the present study.…”
mentioning
confidence: 45%
“…and Goodnight et al (1982) Changes in lipoprotein metabolism also might result in redistribution of cholesterol between plasma and tissues, a fifth mechanism suggested for the hypocholesterolemic effect of dietary polyunsaturates. Several early reports suggested this mechanism of action (Spritz et al, 1963;Bloomfield, 1964;Avigan and Steinberg, 1965;Bieberdorf and Wilson, 1965;Spritz et al, 1965;). Both and Goodnight et al (1982) Wiggers et al, 1977b;Barrows et al, 1980;Richard et al, 1980), rabbits (Bieberdorf and Wilson, 1965;Richard et al, 1982), rats (Wiggers et al, 1977a;, guinea pigs , squirrel monkeys (Lofland et al, 1970), and pigs Wiggers et al, 1980;.…”
mentioning
confidence: 96%
See 1 more Smart Citation